Baicalin Inhibits Ferroptosis in Intracerebral Hemorrhage - Duan, Lining; Zhang, Ying; Yang, Yuna; Su, Shiyu; Zhou, Ligui; Lo, Po-Chieh; Cai, Jiaying; Qiao, Yiqi; Li, Min; Huang, Shuiqing; Wang, Hong; Mo, Yousheng; et al. (Frontiers in Pharmacology, 2021)
Intracerebral hemorrhage (ICH) is a subtype of stroke characterized by high mortality and disability rates. To date, the exact etiology of ICH-induced brain injury is still unclear. Moreover, no curative therapy that can prevent or mitigate disease progression is available. Increasing evidence suggests that ferroptosis plays a dominant role in the pathogenesis of ICH injury. Baicalin is the main active ingredient of the Chinese herbal medicine Scutellaria baicalensis. It has been reported to exhibit neuroprotective effects against ICH-induced brain injury as well as reduce iron deposition in multiple tissues. Therefore, in this study, we focused on the protective mechanisms of baicalin against ferroptosis caused by ICH using the hemin-induced in vitro model and the Type IV collagenase-induced in vivo model. Our results revealed that baicalin enhanced cell viability and suppressed ferroptosis in rat pheochromocytoma PC12 cells treated with hemin, erastin and RSL3. Forthermore, Baicalin alleviated motor deficits and brain injury in ICH model mice by inhibiting ferroptosis. Evidently, ferroptosis is a key pathological feature of ICH and baicalin prevents the development of ferroptosis in ICH. As such, baicalin is a potential therapeutic drug for ICH treatment.